Vitiligo Extent Tensity Index (VETI) score: a new definition, assessment and treatment evaluation criteria in vitiligo - Amir Feily (Mattioli1885, 2019)
Although skin is the largest organ of the body, there are no standardized reproducible methods for assessing severity of many skin diseases. Due to lack of consensus, methods of assessment and inexistence of precise scoring system, there is no application for vitiligo estimation in real practice. In this paper the author describes VETI score as a new treatment evaluation criteria and severity assessment method for vitiligo. This new tool, as does the PASI score in psoriasis, may be able to produce a constant and reproducible number and to help clinical research on vitiligo patients. Additionally, it has a potential to be a source of any computed application for researchers working on vitiligo patients.